Pengelolaan Arsip dalam Menunjang Layanan Informasi pada Bagian Tata Usaha di Madrasah Aliyah Negeri - Aufi Azmi Fu'adah; Nikmatus Sholihah; Masthuroh Masthuroh (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
Good archive management is very important in providing information services so as not to hinder operational activities in madrasas. The purpose of this study is to explain archive management in supporting information services in the administrative section at Madrasah Aliyah Negeri 1 Gresik. The research method used is a qualitative approach with the type of descriptive research. The research site is at Madrasah Aliyah Negeri 1 Gresik. The informants of this research are administrative staff. The results obtained from the study explain that the management of archives at Madrasah Aliyah 1 Gresik which is under the administrative division has been carried out well in supporting information services at the madrasa through several stages: 1) Creating archives through incoming and outgoing letters; 2) The distribution of archives is carried out through the procedures written in the standard operating procedures for distributing letters in madrasas; 3) Archive storage is done by numbering system; 4) Use of archives through retrieval and borrowing of records; 5) Archive maintenance is carried out regularly every two months; 6) Shrinkage of archives is only carried out by transferring archives to the warehouse. However, there are obstacles in its management, namely the absence of archivists, fewer storage cupboards, and no training in archive management. While the supporters are adequate storage warehouse and administrative staff who are painstaking in managing archives.